ANALISIS BEBAN PENCEMAR DAN KAPASITAS ASIMILASI PERAIRAN SUNGAI TAPUNG KIRI KABUPATEN KAMPAR - Resarizki Utami; Bintal Amin; Tengku Nurhidayah (Program Pascasarjana Universitas Riau, 2022)
This research was conducted in September until November 2018 in the Tapung Kiri River Basin in Kampar Regency. Data analyze the water quality conditions in terms of physical, chemical, microbiological and heavy metal parameters, estimating incoming pollutant loads, measuring waters assimilation capacity, and determining pollution index values and the socio-economic impact of the community around the waters of the Tapung Kiri River. Sampling and analysis of samples were carried out at 5 stations with 3 replications carried out both in the field and the laboratory. The results showed that water quality parameters namely TSS, BOD, COD, NH3, PO4, Fe and Total Coliform had exceeded the quality standard based on Government Regulation No. 82 of 2001. The calculation of the pollutant load of the Tapung Kiri River waters indicates that the parameters TSS, BOD, COD, NH3, PO4, Oil and Fe have exceeded their assimilation capacity. The Tapung Kiri River is mild to moderate polluted based on Minister of Environment Decree No. 115 of 2003.